Epithelial Thickness is a Marker of Gastroesophageal Reflux Disease - Vieth, Michael; Mastracci, Luca; Vakil, Nimish; Dent, John; Wernersson, Börje; Baldycheva, Irina; Wissmar, Jenny; Ruth, Magnus; Fiocca, Roberto (Clinical Gastroenterology and Hepatology, 2016)
Background & Aims Histologic criteria have been refined for the diagnosis of gastroesophageal reflux disease (GERD). We aimed to evaluate these criteria for the assessment of GERD and to measure interassessor agreement. Methods We performed a post hoc analysis of data from the Diamond study (NCT 00291746), conducted in Europe and Canada on adults with frequent upper gastrointestinal symptoms who had not taken a proton pump inhibitor in the previous 2 months. GERD was diagnosed based on the presence of 1 or more of the following: reflux esophagitis, pathologic esophageal acid exposure, and/or positive symptom–acid association probability. Nonerosive reflux disease was defined as the presence of pathologic esophageal acid exposure and/or a positive symptom–acid association probability, but no reflux esophagitis. Biopsies collected from 336 patients from 0.5 cm and 2.0 cm above the Z line were evaluable; they were analyzed independently at pathology centers in Germany and Italy (biopsies from 258 and 195 patients, respectively). The primary outcomes were the accuracy of histologic criteria for the diagnosis of GERD, defined by endoscopy and pH monitoring, and interassessor agreement on histologic criteria. Results At the assessment site for basal cell layer thickness, total epithelial thickness was the best-performing criterion for diagnosis of investigation-defined GERD; it also identified nonerosive reflux disease, reflux esophagitis, and pathologic esophageal acid exposure at 0.5 cm and 2.0 cm above the Z line. Basal cell layer thickness and presence of dilated intercellular spaces did not identify patients with GERD. Among the criteria tested, the best agreement between assessments carried out at the 2 pathology centers was for total epithelial thickness at 0.5 cm and 2.0 cm above the Z line. Conclusions Based on an analysis of 336 patients with frequent upper gastrointestinal symptoms, total epithelial thickness is a robust histologic marker for GERD.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Diagnostic; Esophageal Mucosa; Esophagus; Histology